1967
DOI: 10.2466/pr0.1967.20.3.715
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Conditioning, Acceptance of Self and Acceptance of others

Abstract: The experiment concerned the hypotheses that the frequency of self-accepting responses to questionnaire items can be increased by standard verbal conditioning techniques and that this increase generalizes to similar but novel questionnaire items as well as to items indicative of more positive attitudes toward others. Two comparable forms (Forms A and B) of a scale of self-acceptance and acceptance-of-others were used. Form A of the scale, consisting of 18 self-acceptance items and 14 acceptance-of-others items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1972
1972
1976
1976

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Until clinically relevant phenomena can be conditioned and shown to generalize reliably to other behaviour, verbal conditioning will have no significance cither for clinical practice or as a device for studying psychotherapy and other social interaction processes. The present study is essentially an attempt to replicate with hospital patients an investigation reported by Coons and McEachern (1967) using Air Force personnel. As in our earlier study with normals, attitudes towards self and others were chosen as variables which are worthy of investigation since the importance of self-acceptance and acceptance-ofothers has figured prominently in the personality theories of a number of writers (Fromm, 1941;Homey, 1937;Snygg & Combs, 1949;Rogers, 1951Rogers, ,1961.…”
mentioning
confidence: 99%
“…Until clinically relevant phenomena can be conditioned and shown to generalize reliably to other behaviour, verbal conditioning will have no significance cither for clinical practice or as a device for studying psychotherapy and other social interaction processes. The present study is essentially an attempt to replicate with hospital patients an investigation reported by Coons and McEachern (1967) using Air Force personnel. As in our earlier study with normals, attitudes towards self and others were chosen as variables which are worthy of investigation since the importance of self-acceptance and acceptance-ofothers has figured prominently in the personality theories of a number of writers (Fromm, 1941;Homey, 1937;Snygg & Combs, 1949;Rogers, 1951Rogers, ,1961.…”
mentioning
confidence: 99%